Queering la reflexividad etnográfica - Heuser, Ali (2025)
This article explores the intersections of gender and power in the Peruvian Andes where local populations are affected by large-scale mining operations framed within extractivist and patriarchal structures. Aiming to develop an ethnographic reflection on queerness in research the study highlights the challenges of negotiating multiple positionalities through the lens of qualitative fieldwork experience. The article reflects on the methodological strategies employed to address tensions and patriarchal power dynamics in the field, offering new perspectives on ethnographic research in regions where the control of bodies and territories is contested due to mining activity.